Nonlinear optical effects in one- and two-layer metal structures - Khmelinskii, Igor (2020)
In this study, we determined the spectral properties and frequency summing that induced superemission (SE) in two assemblies (A and B) built from a Co nanolayer and a Co nanotrack, which differed in terms of their topography. We found that homogeneous Co films with layer thicknesses of 7.101 and 11.755 nm produced discrete absorption spectra, which originated from the transverse quantum confinement operating in these metal films. The surface plasmon resonance in these films appeared at energies over 50000 cm(-1) where a longer wavelength tail was readily observable. All of the nanolayers considered had discrete emission spectra and the emission bands strongly overlapped due to the large bandwidths. Their emission decay was described by a single-exponential function with lifetimes of 167 +/- 5 and 231 +/- 7 ns for assemblies A and B, respectively. Similarly, the absorption spectrum for the two-layer sandwich assembly comprised the superposition of the respective spectra for the individual Co nanolayers. We found that these assemblies could sum the pumping radiation photons to produce photons with higher energy. After exciting the 11.755 nm Co nanolayer to a given transition, the Co nanotrack produced emission at close to double the energy. We identified this emission as SE and the bandwidths were only about 32 +/- 0.5 and 21 +/- 3 cm(-1) for assemblies A and B, respectively. The SE band appeared with the build-up time of 32 +/- 2 ns for assembly A and 21 +/- 1 ns for assembly B, and disappeared with decay times of 143 +/- 5 and 113 +/- 4 ns, respectively. We analyzed the energy transfer in detail based on the exchange mechanism, and the eventual contribution of the electric dipole-dipole mechanism was also estimated.